The Effectiveness of Digital Technologies Used for the Visitor’s Experience in Digital Museums. A Systematic Literature Review from the Last Two Decades - Ahdab Najib Hijazi; Ahmad Hanif Ahmad Baharin (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The rapid advancement of technology has created a vibrant digital museum services and solutions industry. There is a drive for museums to overcome interaction and engagement issues, therefore providing a favorable atmosphere for a digital heritage economy. The research objectives of this paper are the recognition of the digital technologies used for the growth of digital museums. The study used the PRISMA statement 2020 to investigate the powerful technologies applied to the digital museum to develop the visitor’s experience. The final 46 articles included for the investigation and VOS software and key occurrence terms find the major classification themes of the literature. The digital museums, visitors’ experiences, and digital technologies. The study’s findings indicated that digital technologies significantly impact visitors’ experience and interest after digital technologies like AR and VR development. In addition, many new inclusions of digital technologies like Personalization / Wearable Devices, Gesture Technology / Non-touch Interactives, Mobile Technologies, Indoor GPS tracking systems, Artificial Intelligence, Flexible Technology Exhibit Platforms, Virtual Touring, and clouding are also enhancing the visitor’s experience in museums.